The efficiency of BRICS countries in sustainable development: A data envelopment analysis - Gebert, Isabella Melissa Muller (2023)
Economic growth has traditionally been the main way to evaluate a country’s development, and its intense pursuit usually comes at a great environmental cost to the nations. The growing concern regarding the adverse consequences of economic growth on the environment and people’s well-being has encouraged economists to find new approaches to assess the countries’ development, considering environmental and social metrics rather than only the Gross Domestic Product. Emerging countries have become relevant players in the international system due to their fast-growing economies, large populations, and abundant ecological assets. The BRICS are composed of a heterogeneous group of nations, distinct in their political structure and economic activities, whose leaders have often met aiming to articulate cooperative policies and strategies to improve their collective growth. Not only have they turned into major economies, but also major greenhouse gas emitters. Therefore, it becomes necessary to analyze if their economic growth meets sustainable development. This thesis aims to analyze the BRICS countries’ efficiencies in turning their productive resources, which are also considered to be drivers of their economic growth, into sustainable development. The objective was achieved by using the data envelopment analysis technique, to create efficiency scores according to each of the three pillars of sustainability (economic, environmental, and social). The comparative results enable the possibility to better understand the countries’ challenges towards sustainable development, and to be subject to further scientific explorations.